Composite material for explosion-proof tank, preparation method of composite material and explosion-proof tank
By using unsaturated polyester composite materials and modified graphene oxide, a composite material for explosion-proof box with high safety and mechanical properties was prepared, which solved the problem of leakage risk of existing explosion-proof box.
Patent Information
- Application Number
- CN202411569100.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-02-18
AI Technical Summary
The existing explosion-proof boxes have a risk of leakage due to metal materials, resulting in safety hazards.
Unsaturated polyester composite materials are used as electrostatic materials, with semi-insulating and semi-conductive properties, and combined with glass fiber and modified graphene oxide, composite materials with high bending strength and impact toughness are prepared.
It effectively eliminates the hidden danger of explosion caused by arc accumulation, greatly improves the safety of explosion-proof boxes, and improves the mechanical properties of composite materials.
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of explosion-proof boxes, and in particular to a composite material for explosion-proof boxes, a preparation method thereof, and an explosion-proof box. Background Art
[0002] Explosion-proof boxes generally include explosion-proof junction boxes, explosion-proof terminal boxes, explosion-proof distribution boxes, explosion-proof distribution cabinets, etc., and these explosion-proof boxes are generally made of aluminum, and the cable brackets and other electrical accessories in the explosion-proof boxes are made of metal. Metal has good conductivity. If the electrical components of the explosion-proof boxes and cable brackets made of metal leak electricity, the staff will be directly electrocuted when they touch them, which poses a great safety hazard. Summary of the invention
[0003] In order to reduce the potential safety hazard of electric leakage in an explosion-proof box, the present application provides a composite material for an explosion-proof box, a preparation method thereof, and an explosion-proof box.
[0004] In a first aspect, the present application provides a composite material for an explosion-proof box, which adopts the following technical solution: A composite material for an explosion-proof box comprises the following raw materials in parts by weight: 18-22 parts of unsaturated polyester, 6-10 parts of a low profile shrinkage agent, 0.3-0.7 parts of a high-activity initiator, 1.5-2.5 parts of an internal release agent, 0.2-0.6 parts of a thickener, 25-35 parts of a flame retardant, 30-38 parts of glass fiber, 0-3 parts of an internal coloring pigment and 2.5-3.6 parts of an auxiliary agent.
[0005] By adopting the above technical solution, the present application adopts non-metallic materials as explosion-proof box materials and unsaturated polyester composite materials as electrostatic materials, which have semi-insulating and semi-conductive properties, and can slowly release the arc outward, effectively eliminating the hidden danger of explosion caused by arc accumulation, greatly improving the safety of the explosion-proof box, and through the selection and proportion of raw materials, its bending strength can reach 172MPa, and its impact toughness can reach 120kJ / m 2 , which can meet the application requirements of explosion-proof boxes.
[0006] Preferably, the composite material for explosion-proof box further comprises 0.1-1.2 parts by weight of silane coupling agent.
[0007] By adopting the above technical solution and adding a silane coupling agent, the compatibility between the glass fiber, the inorganic particles and the system can be improved, and the interface pores between the glass fiber and the system can be effectively reduced, thereby improving the mechanical properties of the composite material.
[0008] Preferably, the composite material for explosion-proof box further comprises 0.003-0.007 parts by weight of modified graphene oxide, wherein the modified graphene oxide is prepared by grafting graphene oxide with a silane coupling agent and a maleic acid copolymer.
[0009] By adopting the above technical solution, since graphene oxide is an inorganic material, its compatibility with the composite material system is insufficient. If it is directly added, it is easy to agglomerate in the system. The inventors of the present application first copolymerize the silane coupling agent with maleic acid, and then connect the obtained copolymer to the surface of graphene oxide through an esterification reaction, which can increase the compatibility of graphene oxide with the system, and the copolymer can increase the molecular distance between graphene oxide, making it difficult to agglomerate. Therefore, through modification, the interface gap between graphene oxide and the system can be greatly reduced, making the integrity of the composite material stronger, and the improvement of the mechanical properties of the composite material by graphene oxide is greater.
[0010] Preferably, the preparation method of the modified graphene oxide is as follows: S1, copolymerizing 23-27 parts by weight of a mixed monomer of a silane coupling agent containing a double bond and maleic acid under the action of 0.003-0.005 parts by weight of azobisisobutyronitrile or azobisisoheptanenitrile to obtain a copolymer of a silane coupling agent and maleic acid; the maleic acid accounts for 12-28% of the total weight of the mixed monomer; S2. In-situ grafting of graphene oxide with a silane coupling agent and a maleic acid copolymer through an esterification reaction; the weight ratio of graphene oxide to the silane coupling agent and the maleic acid copolymer is 1:(22-27).
[0011] By adopting the above technical scheme, the graphene oxide can be successfully grafted with the organic copolymer through the reaction of the carboxyl group in the copolymer and the hydroxyl group on the surface of the graphene oxide, and the copolymer can react more with the surface of the graphene oxide rather than the edge, which can better improve its compatibility with the system.
[0012] Preferably, the preparation method of the modified graphene oxide is as follows: S1, treating the surface of calcium carbonate with a cationic surfactant, and then mixing and reacting with graphene oxide to obtain a calcium carbonate-loaded graphene oxide composite material; S2, copolymerizing 23-27 parts by weight of a mixed monomer of a silane coupling agent containing a double bond and maleic acid under the action of 0.003-0.005 parts by weight of azobisisobutyronitrile or azobisisoheptanenitrile to obtain a copolymer of a silane coupling agent and maleic acid; the maleic acid accounts for 12-28% of the total weight of the mixed monomer; S3, in-situ grafting of a silane coupling agent and a maleic acid copolymer onto the calcium carbonate-loaded graphene oxide composite material through an esterification reaction; the weight ratio of the calcium carbonate-loaded graphene oxide composite material to the silane coupling agent and the maleic acid copolymer is 2:(22-27); S4. Treat the product obtained in S3 with acid to remove calcium carbonate, and then treat it with ultrasound to obtain a rolled modified graphene oxide.
[0013] By adopting the above technical scheme, graphene oxide is adsorbed on the surface of calcium carbonate particles through electrostatic action, and then the exposed side is grafted with copolymers, and then the calcium carbonate is melted. Due to the huge surface tension difference between the two sides, the graphene oxide of the grafted copolymer is very easy to roll under the action of ultrasound. Then the copolymer grafted on its surface is more exposed, so that the obtained modified graphene oxide is more compatible with the system, and after rolling, the modified graphene oxide has stronger dispersibility. Under comprehensive conditions, after the modified graphene oxide is rolled, the mechanical properties of the composite material for explosion-proof boxes prepared are stronger.
[0014] Preferably, the particle size of the calcium carbonate is 20-50 μm.
[0015] By adopting the above technical solution, the diameter of graphene oxide is micron-level, and calcium carbonate within this particle size range can better load graphene oxide.
[0016] In a second aspect, the present application provides a method for preparing a composite material for an explosion-proof box, using the following technical solution: A method for preparing a composite material for an explosion-proof box comprises the following steps: S1. Mix 25-35℃ unsaturated polyester and low profile shrinkage agent, then add high activity initiator and auxiliary agent, and continue to stir and mix; S2, add internal coloring pigment, internal release agent, flame retardant, and the remaining raw materials except thickener in sequence, stir and mix; finally, add thickener and stir evenly; S3. The mixed material obtained in S2 is cured in a drying room at 37-45° C., stacked according to thickness after curing, and cured in a high-temperature mold at a temperature of 120-150° C. to obtain an explosion-proof box composite material.
[0017] By adopting the above technical scheme, in the preparation method of the present application, stirring and mixing can be carried out in the order of addition. The preparation method is relatively conventional, does not require special processes or equipment modifications, and the qualified rate of the prepared products is high, which is suitable for large-scale production.
[0018] In a second aspect, the present application provides a method for preparing a composite material for an explosion-proof box, using the following technical solution: An explosion-proof box, wherein the explosion-proof box is made of the composite material for explosion-proof box according to any one of claims 1 to 6.
[0019] In summary, the present application includes at least one of the following beneficial technical effects: 1. This application adopts non-metallic materials as explosion-proof box materials and unsaturated polyester composite materials as electrostatic materials. It has semi-insulating and semi-conductive properties, can slowly release the arc outward, effectively eliminates the hidden danger of explosion caused by arc accumulation, and greatly improves the safety of the explosion-proof box.
[0020] 2. Graphene oxide is adsorbed on the surface of calcium carbonate particles through electrostatic action, and then the exposed side is grafted with copolymers. Then the calcium carbonate is melted. Due to the huge surface tension difference between the two sides, the graphene oxide grafted with copolymers is very easy to roll under the action of ultrasound. Then the copolymer grafted on its surface is more exposed, making the modified graphene oxide more compatible with the system, and after rolling, the modified graphene oxide has stronger dispersibility. Under comprehensive conditions, after the modified graphene oxide is rolled, the mechanical properties of the composite material for explosion-proof boxes are stronger.
[0021] 3. Through the selection and proportioning of raw materials, the bending properties of the composite materials for explosion-proof boxes in this application can reach 172MPa, and the impact toughness can reach 120kJ / m2; on this basis, the inventors have developed graphene oxide and prepared rolled modified graphene oxide, so that the bending properties of the composite materials for explosion-proof boxes can reach a maximum of 224MPa, and the impact toughness can reach a maximum of 163MPa; explosion-proof boxes with better performance can be produced, and the application potential is greater. DETAILED DESCRIPTION
[0022] The present application is further described in detail below in conjunction with the specific contents.
[0023] raw material The raw materials used in the preparation examples and embodiments of this application can be purchased from the market. Among them, the thickness of graphene oxide is about 1 nm, the number of layers is 1-2, the average diameter of the flakes is 30 μm, and the specific surface area is 200 m 2 / g, purity>95wt%; the model of unsaturated polyester is 196; the high activity initiator is TBPO, the content is 97%; the low profile shrinkage agent is polystyrene, the model is H814-902; the internal release agent is zinc stearate, CAS No. 557-05-1; the thickener is active magnesium oxide, the model is 600; the flame retardant is aluminum hydroxide, the particle size is 8000 mesh; the model of the auxiliary agent is BYK-301; the internal coloring pigment is cobalt blue, the model is 001; the glass fiber is alkali-free glass fiber, the length is 3.0mm.
[0024] Preparation Example Preparation Example 1 A modified graphene oxide, the preparation method of which is as follows: S1. Prepare 100 mL of a cationic surfactant with a concentration of 0.1 mol / L, then add 1 g of calcium carbonate, stir for 1 hour, and then filter to obtain surface-treated calcium carbonate; the particle size range of the calcium carbonate is 20-50 μm; the cationic surfactant is dodecyltrimethylammonium chloride; S2, adding 0.1 g of graphene oxide to water, ultrasonically dispersing for 30 min, then stirring for 10 min, adding the surface-treated calcium carbonate of S1, stirring for 10 min, and then filtering to obtain a calcium carbonate-loaded graphene oxide composite material; S3. Under nitrogen atmosphere, 25 g of monomers were added to 50 g of DMAC, wherein the monomers included a silane coupling agent containing a double bond and maleic acid, and the weight ratio of the silane coupling agent containing a double bond to maleic acid was 20:5. The mixture was stirred until dissolved, and then 0.004 g of azobisisobutyronitrile was added. The mixture was heated to 70° C. and stirred for reaction for 20 h. The solvent was then removed by rotary evaporation to obtain a copolymer of a silane coupling agent and maleic acid. The silane coupling agent containing a double bond was vinyltriethoxysilane. S4. Under a nitrogen atmosphere, 2 g of calcium carbonate-supported graphene oxide composite material was added to 50 g of DMAC, and after stirring and dispersing, 5 g of silane coupling agent and maleic acid copolymer were added, and stirred until dissolved. Then, 15 g of toluene was added as a water-carrying agent, and 0.2 g of p-toluenesulfonic acid was added as a catalyst, and stirred until dissolved. The temperature was raised to 150 ° C., stirred for reaction for 18 h, cooled to room temperature, and filtered to obtain a calcium carbonate-supported graphene oxide grafted organic copolymer composite material; S5. Add 0.2 mol / l of dilute hydrochloric acid to the calcium carbonate-supported graphene oxide grafted organic copolymer composite material until no bubbles are generated, then ultrasonically treat the mixed solution for 20 minutes, filter, and dry to obtain a rolled graphene oxide grafted organic copolymer composite material, i.e., modified graphene oxide.
[0025] Preparation Example 2 A modified graphene oxide, which is different from Preparation Example 1 in that the weight ratio of the double-bond silane coupling agent and maleic acid is 22:3, and the remaining steps are the same as Preparation Example 1.
[0026] Preparation Example 3 A modified graphene oxide, which is different from Preparation Example 1 in that the weight ratio of the double-bond silane coupling agent and maleic acid is 18:7, and the remaining steps are the same as Preparation Example 1. Example
[0027] Example 1 A composite material for explosion-proof box, the raw materials and the amount of each raw material are shown in Table 1, and the preparation method is as follows: S1. At 30°C, mix the unsaturated polyester and the low profile shrinkage agent and stir for 45 seconds, then add the high activity initiator and the auxiliary agent, and continue to stir for 30 seconds; S2, continue to add internal coloring pigment and stir for 45 seconds; S3, continue to add internal release agent and stir for 30 seconds; S4, raise the temperature to 36°C, add flame retardant, and stir for 120 seconds; S5, heating to 38°C, finally adding thickener, stirring for 65s to obtain a mixture; S6. The mixture obtained in S5 is cured in a drying room at 40° C. for 48 hours. After curing, the mixture is stacked according to thickness and cured in a high-temperature mold at 130° C. for 8 minutes to obtain an explosion-proof box composite material.
[0028] Table 1 Raw materials and amounts of raw materials in Example 1 (kg) Unsaturated polyester 20 Low profile shrinkage agent 8 Highly active initiator 0.5 Internal release agent 2 Thickener 0.4 Flame retardants 30 Fiberglass 34 Internal coloring pigments 2 Additives 3.1 Example 2 A composite material for explosion-proof boxes, which is different from Example 1 in that its raw materials also include 0.5 kg of silane coupling agent KH550, which is added after the flame retardant is added in S4, and the remaining steps are the same as in Example 1.
[0029] Example 3 A composite material for explosion-proof box, which is different from Example 2 in that its raw materials also include 0.005 kg of modified graphene oxide, which is added before adding the thickener in S5, and the preparation method of the modified graphene oxide is as follows: S1. Under nitrogen atmosphere, add 25 g of monomer to 50 g of DMAC, the monomer includes a silane coupling agent containing a double bond and maleic acid, the weight ratio of the silane coupling agent containing a double bond to maleic acid is 20:5, stir until dissolved, then add 0.004 g of azobisisobutyronitrile, heat to 70 ° C, stir and react for 20 hours, then remove the solvent by rotary evaporation to obtain a copolymer of silane coupling agent and maleic acid; S4. Under a nitrogen atmosphere, add 0.2 g of graphene oxide to 50 g of DMAC, stir and disperse, add 5 g of silane coupling agent and maleic acid copolymer, stir until dissolved, then add 100 g of toluene as a water-carrying agent, add 0.2 g of p-toluenesulfonic acid as a catalyst, stir until dissolved, heat to 150 ° C, stir and react for 18 hours, cool to room temperature, filter, and dry to obtain modified graphene oxide.
[0030] Example 4 A composite material for explosion-proof boxes, which is different from Example 2 in that its raw materials also include 0.005 kg of modified graphene oxide, the modified graphene oxide comes from Preparation Example 1, and the remaining steps are the same as Example 2.
[0031] Example 5 A composite material for explosion-proof boxes, which is different from Example 4 in that the modified graphene oxide comes from Preparation Example 2, and the remaining steps are the same as Example 4.
[0032] Example 6 A composite material for explosion-proof boxes, which is different from Example 4 in that the modified graphene oxide comes from Preparation Example 3, and the remaining steps are the same as Example 4.
[0033] Example 7 A composite material for explosion-proof boxes, which is different from Example 4 in that the added amount of modified graphene oxide is 0.003 kg, and the remaining steps are the same as those of Example 4.
[0034] Example 8 A composite material for explosion-proof boxes, which is different from Example 4 in that the added amount of modified graphene oxide is 0.007 kg, and the remaining steps are the same as those of Example 4.
[0035] Comparative Example Comparative Example 1 A composite material for explosion-proof boxes, which is different from Example 3 in that its modified graphene oxide is replaced by graphene oxide of equal mass, and the remaining steps are the same as those of Example 3.
[0036] Performance testing Detection method / test method Composite materials for explosion-proof boxes were prepared according to the preparation methods of Examples 1-8 and Comparative Example 1, and then tested according to the following testing method. The test results are shown in Table 2.
[0037] Bending strength: tested according to the test method in GB / T1449-2005; Impact toughness (unnotched): tested according to the testing method in GB / T1451-2005.
[0038] Table 2 Test results of Examples 1-8 and Comparative Example 1 Bending strength(MPa) <![CDATA[Impact toughness (kJ / m 2 )]]> Example 1 172 120 Example 2 178 122 Example 3 201 150 Example 4 224 163 Example 5 219 159 Example 6 215 157 Example 7 206 154 Example 8 226 166 Comparative Example 1 183 144 Through Examples 1-8 and Comparative Example 1, as well as the test data in Table 2, it can be seen that the present application uses non-metallic materials as explosion-proof box materials and unsaturated polyester composite materials as electrostatic materials, which have semi-insulating and semi-conductive properties, and can slowly release the arc outward, effectively eliminating the hidden danger of explosion caused by arc accumulation, and greatly improving the safety of the explosion-proof box. Through the selection and proportion of raw materials, the present application can achieve a bending performance of 172MPa and an impact toughness of 120kJ / m 2 On this basis, the inventors conducted research and development on graphene oxide and prepared rolled modified graphene oxide, so that the bending properties of the composite materials for explosion-proof boxes reached a maximum of 224MPa, and the impact toughness reached a maximum of 163MPa; explosion-proof boxes with better performance can be produced, with greater application potential.
[0039] It can be seen from the test data of Example 1 and Example 2 that by adding a silane coupling agent, the compatibility between the glass fiber and the system can be improved, and the interface pores between the glass fiber and the system can be effectively reduced, thereby improving the mechanical properties of the composite material.
[0040] Since graphene oxide is an inorganic material, it is not compatible with the composite material system. If it is directly added, it is easy to agglomerate in the system. The inventor of the present application first copolymerizes a silane coupling agent with maleic acid, and then connects the obtained copolymer to the surface of graphene oxide through an esterification reaction, which can increase the compatibility of graphene oxide with the system, and the copolymer can increase the molecular distance between graphene oxides, making it difficult to agglomerate. Therefore, through modification, the interface gap between graphene oxide and the system can be greatly reduced, making the integrity of the composite material stronger, and the improvement of the mechanical properties of the composite material by graphene oxide is greater. This can be verified by the test data of Example 3 and Comparative Example 1.
[0041] The inventor further studied the modified graphene and found that the graphene oxide was adsorbed on the surface of calcium carbonate particles by electrostatic action, and then the exposed side was grafted with copolymers, and then the calcium carbonate was melted. The graphene oxide of the grafted copolymer was very easy to roll up under the action of ultrasound due to the huge surface tension difference on both sides. Then the copolymer grafted on its surface was more exposed, so that the obtained modified graphene oxide was more compatible with the system, and after rolling, the dispersibility of the modified graphene oxide was stronger. Under comprehensive conditions, after the modified graphene oxide was rolled, the mechanical properties of the composite material for explosion-proof boxes prepared were stronger. This can be verified by the test data of Example 3-4.
[0042] It can be seen from the test data of Examples 4-6 that the addition ratio of the silane coupling agent and maleic acid in the copolymer during preparation is also a factor affecting the mechanical properties of the composite material. It is speculated that after the copolymerization of the silane coupling agent, the effect of the silicone softener can be exerted, so that the composite material can have its toughness enhanced while improving the mechanical strength. Therefore, the bending strength and impact toughness of the composite material are improved. While copolymerization with maleic acid can utilize the carboxyl group on the maleic acid to be grafted with the hydroxyl group on the graphene oxide through esterification reaction, the carboxyl group contained in it can also be conjugated with the benzene ring structure of graphene oxide through p-π, so that the copolymer is more adsorbed on the surface of graphene oxide, which can reduce its surface tension to a greater extent and improve its compatibilizer.
[0043] It can be seen from the test data of Example 4 and Examples 7-8 that when the amount of modified graphene oxide added is gradually increased, the mechanical properties of the composite material are gradually improved. However, when the amount of addition is increased from 0.005kg to 0.007kg, the improvement of the mechanical properties is small. Therefore, considering the comprehensive production cost, 0.005kg is the optimal addition amount.
[0044] This specific embodiment is merely an explanation of the present invention and is not a limitation of the present invention. After reading this specification, those skilled in the art may make non-creative modifications to the present embodiment as needed. However, as long as they are within the scope of the claims of the present invention, they are protected by the patent law.
Claims
1. A composite material for explosion-proof boxes, characterized in that: The invention comprises the following raw materials in parts by weight: 18-22 parts of unsaturated polyester, 6-10 parts of low profile shrinkage agent, 0.3-0.7 parts of high activity initiator, 1.5-2.5 parts of internal mold release agent, 0.2-0.6 parts of thickener, 25-35 parts of flame retardant, 30-38 parts of glass fiber, 0-3 parts of internal coloring pigment and 2.5-3.6 parts of auxiliary agent.
2. The composite material for explosion-proof box according to claim 1, characterized in that: The composite material for explosion-proof box further comprises 0.1-1.2 parts by weight of silane coupling agent.
3. The composite material for explosion-proof box according to claim 2, characterized in that: The composite material for explosion-proof box also includes 0.003-0.007 parts by weight of modified graphene oxide, and the modified graphene oxide is prepared by grafting graphene oxide with a silane coupling agent and a maleic acid copolymer.
4. The composite material for explosion-proof box according to claim 3, characterized in that: The preparation method of the modified graphene oxide is as follows: S1, copolymerizing 23-27 parts by weight of a mixed monomer of a silane coupling agent containing a double bond and maleic acid under the action of 0.003-0.005 parts by weight of azobisisobutyronitrile or azobisisoheptanenitrile to obtain a copolymer of a silane coupling agent and maleic acid; the maleic acid accounts for 12-28% of the total weight of the mixed monomer; S2. In-situ grafting of graphene oxide with a silane coupling agent and a maleic acid copolymer through an esterification reaction; the weight ratio of graphene oxide to the silane coupling agent and the maleic acid copolymer is 1:(22-27).
5. The composite material for explosion-proof box according to claim 3, characterized in that: The preparation method of the modified graphene oxide is as follows: S1, treating the surface of calcium carbonate with a cationic surfactant, and then mixing and reacting with graphene oxide to obtain a calcium carbonate-loaded graphene oxide composite material; S2, copolymerizing 23-27 parts by weight of a mixed monomer of a silane coupling agent containing a double bond and maleic acid under the action of 0.003-0.005 parts by weight of azobisisobutyronitrile or azobisisoheptanenitrile to obtain a copolymer of a silane coupling agent and maleic acid; the maleic acid accounts for 12-28% of the total weight of the mixed monomer; S3, in-situ grafting of a silane coupling agent and a maleic acid copolymer onto the calcium carbonate-loaded graphene oxide composite material through an esterification reaction; the weight ratio of the calcium carbonate-loaded graphene oxide composite material to the silane coupling agent and the maleic acid copolymer is 2:(22-27); S4. The product obtained in S3 is treated with acid to remove calcium carbonate, and then subjected to ultrasonic treatment to obtain rolled modified graphene oxide.
6. The composite material for explosion-proof box according to claim 5, characterized in that: The particle size of the calcium carbonate is 20-50 μm.
7. A method for preparing the composite material for explosion-proof box according to any one of claims 1 to 6, characterized in that: It includes the following steps: S1. Mix and stir the 25-35℃ unsaturated polyester and low profile shrinkage agent, then add the high activity initiator and auxiliary agent, and continue to stir and mix; S2, add internal coloring pigment, internal release agent, flame retardant, and the remaining raw materials except thickener in sequence, stir and mix; finally, add thickener and stir evenly; S3. The mixed material obtained in S2 is cured in a drying room at 37-45° C., stacked according to thickness after curing, and cured in a high-temperature mold at a temperature of 120-150° C. to obtain an explosion-proof box composite material.
8. An explosion-proof box, characterized in that: The explosion-proof box is made of the composite material for explosion-proof boxes according to any one of claims 1-6.
Citation Information
Cited By
Graphene modified epoxy resin-based packaging material and preparation method thereof
CN120464140A